STUDYING THE INFLUENCE OF THE LENGTH OF TERMINAL THIOALKYL GROUPS ON THE LIQUID CRYSTALLINE PROPERTIES OF IMINE-ESTER BENZOTHIAZOLE - Nwyr, Nizar S.; Al-Hamdani, Uhood J.; Alsalim, Tahseen A. (International Journal Multidisciplinary (IJMI), 2026)
Objective: A chain of new calamitic liquid crystals, featuring a heterocyclic (benzothiazole) core structure with two phenyl rings, a terminal thioalkyl string, and azomethene and ester linkages, were synthesized and described. This chain comprises of seven compounds, differentiated by the length of the thioalkyl string (-SRn, n = 1, 2, 4–8). Method: The results of the spectral study aligned with the anticipated structure. The structures of synthesized compounds were verified via various spectroscopic methods, including 1H-NMR, 13C-NMR, mass spectrometry, and FT-IR spectroscopy. Differential scanning calorimetry (DSC) and polarizing optical microscopy (POM) have been utilized to confirm their mesomorphic properties. Theoretical computations were performed via the density functional theory (DFT) approach at the CAM-B3LYP/6-311G (2d,p) level. Results: Only the nematic phase was noticed for the first and second compounds of the chain (n = 1, 2). With the increase length of the thioalkyl chain to n = 4, 5, 6, the nematic phase emerged alongside an extra smectic phase. Upon transitioning from n = 7 to the maximum compound n = 8, the nematic phase vanished, and these members alone displayed the Smectic phase (SmA). (DFT) data were correlated with empirical data from liquid crystalline studies, revealing that the molecular architecture, reactivity, dipole moment, aspect ratio, and polarizability of the examined members are significantly influenced by the length of the terminal chain. Novelty: A chain of new calamitic liquid crystals, featuring a heterocyclic (benzothiazole) core structure with azomethene and ester linkages and a terminal thioalkyl string, were synthesized and described, with properties significantly influenced by the length of the terminal chain.